Peningkatan minat dan hasil belajar IPA melalui model pembelajaran think pair share - Devi Kurniasih (Universitas Sarjanawiyata Tamansiswa, 2018)
This research purpose to determine the increase in interest and science learning outcomes of through the implementation of cooperative learning model Think Pair Share (TPS). This type of research is classroom action research (PTK). interest and science learning outcomes increased by 14.82%. This can be indicated by the increase of the average percentage of student interest based on the questionnaire results for each cycle, ie in the first cycle of 73.43% increased to 79.82% in Cycle II. At pre-cycles, the percentage of completeness is 35.71% or 10 completed students. Once given a cycle action one percentage of mastery increases to 60.71% or 17 completed students. Then in cycle two has increased to 100% or all students experience mastery with an average value of 84.46. Â